Effect of Ionic Liquid on the Determination of Aromatic Amines as Contaminants in Hair Dyes by Liquid Chromatography Coupled to Electrochemical Detection - Lizier, Thiago Mescoloto [UNESP] (2012)
The room temperature ionic liquid (IL) 1-butyl-3-methylimidazolium bis-(trifluorometanesulfonyl) imide BMIm[NTf2] was used as a novel medium for improvement of separation and quantization of 16 aromatic amines typically present as contaminants in consumer products and detected by HPLC coupled to an electrochemical detector. The aromatic amines, namely 4,4'-diaminodiphenylmethane, 4-chloroaniline, 2-methoxy-5-methyl-aniline, 3,3'-dimethylbenzidine, 2,4-diaminotoluidine, 2-chloro-4-nitroaniline, 4,4'-oxydianiline, aniline, 3,3'-dichlorobenzidine, benzidine, 4-aminobiphenyl, o-dianisidine, o-anisidine, o-toluidine, 4,4'-methylene-bis-2-chloroaniline and 2-naphthylamine are oxidized in methanol/BMIm[NTf2] at a potential around +0.68V to +0.93V vs. Ag/AgCl at a glassy carbon electrode, which is the base for their determination by HPLC/ED. Using the optimized conditions of methanol/BMIm[NTf2] 70: 30 (v/v) as mobile phase, flow-rate of 0.8 mL.min(-1), column CLC-ODS, E-ap = +1.0 V and T = 40 C analytical curves were constructed for each of the tested amines. Good linearity was obtained in the concentration range of 1.09 mg.L-1 to 217 mg.L-1, with excellent correlation coefficients. The limits of detection reached 0.021 mg.L-1 to 0.246 mg.L-1 and good relative standard deviations (RSD, n = 3) were obtained from the measurements. Satisfactory recovery for each aromatic amine was achieved, ranging from 95 to 103%. The developed method was successfully applied to determine six aromatic amines present as contaminants in commercial hair dye samples.